Predictors of Pediatric Tracheostomy Outcomes in the United States. (September 2020) - Friesen, Tzyynong L.; Zamora, Steven M.; Rahmanian, Ronak; Bundogji, Nour; Brigger, Matthew T.
Objectives: To investigate the outcomes of pediatric tracheostomy as influenced by demographics and comorbidities. Study Design: Retrospective national database review. Setting: Fifty-two children's hospitals across the United States. Subjects and Methods: Hospitalization records from Pediatric Health Information System database dated 2010 to 2018 with patients younger than 18 years and procedure codes for tracheostomy were extracted. The primary outcome was total length of stay. The secondary outcomes were 30-day readmission, mortality, and posttracheostomy length of stay. Results: A total of 14, 155 children were included in the analysis. The median total length of stay was 77 days and increased from 59 to 103 days between 2010 and 2018 ( P < .001). The median posttracheostomy length of stay was 34 days and also increased from 27 to 49 days ( P < .001). On multivariate regression analyses, the total and posttracheostomy lengths of stay were significantly increased in children younger than 1 year, patients of black race, hospitals in the non-West regions, those discharged to home, and those with comorbidities. Socioeconomic indicators such as insurance type and estimated household income were associated with no difference or small effect sizes. Regions and comorbidities were associated with differences in 30-day readmission (overall 26%), while in-hospital mortality was primarily associated with age and comorbidities (overall 8.6%). Conclusion: Pediatric tracheostomy requires substantial health care resources with length of stay escalating over recent years. Age, race, region, discharge destination, and comorbidities were associated with differences in length of stay.